Poly(butylene succinate)-based composites with technical and extracted lignins from wood residues - Melro, Elodie (2024)
Poly(butylene succinate) (PBS) has been drawing attention as a reliable biodegradable and sustainable alternative to synthetic petroleum-based polymers. In this study, PBS-lignin composites were developed using a recently extracted lignin (LA-lignin) from pine wood residues employing an innovative sustainable approach. These composites were systematically compared with PBS-based composites formed with commonly used technical lignins. The molecular weight of the lignins was evaluated, along with various structural and performance-related properties. The LA-lignin/PBS composites display a remarkably low water solubility (ca. < 2%), water uptake (ca. 100 degrees). Moreover, the rigidity and thermal stability of the LA-lignin-PBS composites were higher than those of the systems formed with technical lignins. Although all composites studied present remarkable antioxidant features, the novel LA-lignin-PBS systems stand out in terms of antiadhesion activity against both Gram-positive and Gram-negative bacteria. Overall, the systematic analysis performed in this work regarding the impact of various lignins on the formed PBS composites enables a better understanding of the essential structural and compositional lignin features for achieving biobased materials with superior properties.